Characterization and analysis of Ca-Zn ferrite nanoparticles based flexible metamaterial for sensing applications - Md.Zikrul Bari Chowdhury; Mohammad Tariqul Islam; Iskandar Yahya; Abdulmajeed M. Alenezi; Mohamed S. Soliman; Md. Samsuzzaman (Engineering Science and Technology, an International Journal)
This study presents a flexible Ca-Zn ferrite-based metamaterial designed for microwave sensing application, particularly in the detection of dairy products. The design incorporates a split-ring resonator (SRR) unit cell fabricated on a flexible substrate synthesized through a sol–gel process, integrating PVA glue with Ca-Zn ferrite nanoparticles. Structural characterization through X-ray diffraction (XRD) and field emission scanning electron microscopy (FESEM) confirmed the composite’s structural integrity and electromagnetic suitability. The MTM exhibited multi-frequency resonance at 2.4 GHz, 3.68 GHz, and 7 GHz, with the C-band resonance demonstrating high sensitivity for sensing applications. A key advantage of the design is its flexibility maintaining stable performance under bending angles up to 90 degrees without degrading performance. This work highlights the versatility and adaptability of the proposed metamaterial, making it a promising solution for microwave sensing technologies.